Computer Highlights Society Magazines. - Ward, Bob (Computer (00189162), 2009)
The article features selected articles and issues of Computer Society magazines offering a variety of topics related to computers. These include "What Makes APIs Hard to Learn? Answers from Developers," by Martin P. Robillard, in the December 2009 issue of "Software," "Protecting the DNS from Routing Attacks: Two Alternative Anycast Implementations," by Ioannis Avramopoulos and Martin Suchara, in the September/October 2009 issue of "Security and Privacy" and "IT Productivity = ?," by Linda Wilbanks, in the November/December issue of "IT Professional."